Uptake of 68gallium in atherosclerotic plaques in LDLR-/- ApoB100/100 mice - Silvola J; Laitinen I; Sipilä H; Laine J; Leppänen P; Ylä-Herttuala S; Knuuti J; Roivainen A (Germany, 2025)
Background: Atherosclerosis is a chronic inflammatory disease of artery wall characterized by infiltration of monocytes into subendothelial space and their differentiation into macrophages. Since rupture-prone plaques commonly contain high amounts of activated macrophages, imaging of the macrophage content may provide a useful tool for the evaluation of plaque vulnerability. The purpose of this study was to explore the uptake of 68gallium (68Ga) in atherosclerotic plaques in mice.
Methods: Uptake of ionic 68Ga was investigated in atherosclerotic LDLR-/-ApoB100/100 and C57BL/6N control mice at 3 h after injection. The ex vivo biodistribution of the 68Ga was assessed and autoradiography of aortic cryosections was defined. In vivo imaging of 68Ga was performed using a small animal positron emission tomography PET/CT scanner.
Results: Our results revealed that the uptake of 68Ga-radioactivity was higher in atherosclerotic plaques than in healthy vessel wall (ratio 1.8 +/- 0.2, p = 0.0002) and adventitia (ratio 1.3 +/- 0.2, p = 0.0011). The autoradiography signal co-localized with macrophages prominently as demonstrated by Mac-3 staining. In both mice strains, the highest level of radioactivity was found in the blood.
Conclusions: We observed a moderate but significantly elevated 68Ga-radioactivity uptake in the aortic plaques of atherosclerotic mice, especially at the sites rich in macrophages. While the uptake of 68Ga was promising in this animal model, the slow blood clearance may limit the usability of 68Ga as a PET tracer for clinical imaging of atherosclerotic plaques.